Sistema Avançado de Configuração e Simulação de Unidades Fabris - João Pedro de Jesus Barbosa Pinto (2014)
Simulation is one of the most powerful tools available today for industries wishing to anticipate possible situations or test changes in the functioning of their work processes. A Manufacturing Execution System (MES) is nothing more than a tool that allows a better control over these same procedures, making a bridge between the abstract high-level information systems and the systems that control the machines on the production line. With this project it was possible to understand how one might design a simulation model, and subsequent simulation of that model, of a MES. A study of the major concepts of simulation and related work in the area was carried out to delineate the best strategy to follow and it was concluded that despite the major industrial simulators currently on the market follow a Discrete Event Modeling (DEM) approach, the emerging trend is the Agent Based Simulation (ABS) since this can theoretically obtain best results. Taking this into account, an approaches to solve the problem was developed and implemented, mixing the standardized DEM with the new ABS. The solution was divided into two big steps: the model is created first, through one application, and the simulation is performed after by another one. In the end, it was possible to conclude that since this is an unexplored branch of the simulation the only results we might have are towards the success of a correct simulation, comparing manual executions of the tool that it's being simulated with the simulator itself.